Matrix stiffness controls lymphatic vessel formation through regulation of a GATA2-dependent transcriptional program - Maike Frye; Andrea Taddei; Cathrin Dierkes; Ines Martinez-Corral; Matthew Fielden; Henrik Ortsäter; Jan Kazenwadel; Dinis P. Calado; Pia Ostergaard; Marjo Salminen; Liqun He; Natasha L. Harvey; et al. (Nature Communications, 2018)
Mechanical cues are known to influence endothelial cell behavior. Here Frye et al. show that lymphatic endothelial cell progenitors experience varying degrees of matrix stiffness during development, and that matrix stiffness regulates GATA2 expression to drive lymphatic vessel formation.